Origin of Glomeroporphyritic Clots in the Orthopyroxene Rhyodacite from the Sempah Volcanic Complex, Peninsular Malaysia - A. Ghani, Azman; Navpreet, Singh (Malaysian Journal of Science, 2004)
The Sempah volcanic complex occupies the central part of the Main Range Batholith to the east of Kuala Lumpur. The complex comprises two distinctive porphryritic subvolcanic units that is rhyodacite and orthopyroxene rhyodacite (which contains orthopyroxene phenocrysts). A main textural difference between the rhyodacite and orthopyroxene rhyodacite is the presence of glomeroporphyritic crystal clots in the orthopyroxene rhyodacite, which is not apparent in the rhyodacite. Most of the glomeroporphyritic clots in the orthopyroxene rhyodacite consist of plagioclase, hypersthene, quartz, biotite, microperthite and minor magnetite. The jagged and embayed margins of the crystal clusters where they are in contact with the groundmass can be explained by the quenching of the groundmass. The glomeroporphyritic clots were inferred to be in the process of growth before a quenching event caused the resorption of the crystal margins and subsequently crystallized the groundmass. Therefore, the presence of hypersthene and labradorite in the orthopyroxene rhyodacite can be explained as high-temperature early magmatic phenocryst phases.